Respiratory phenotypes of neuromuscular diseases: A challenging issue for pediatricians - Melissa Borrelli; Gaetano Terrone; Roberto Evangelisti; Flora Fedele; Adele Corcione; Francesca Santamaria (Pediatrics and Neonatology, 2023)
Neuromuscular disease (NMDs) encompass a heterogeneous group of genetic disorders, with respiratory problems of variable intensity and progression described at any pediatric age, from infancy to adolescence, and they are largely associated with significant lifelong morbidity and high mortality. Restriction of breathing, impaired gas exchange, decline of lung function and sleep disordered breathing progressively develop because of muscular weakness and culminate in respiratory failure. Depending on the disease progression, airways manifestations can take weeks to months or even years to evolve, thus depicting two major respiratory phenotypes, characterized by rapid or slow progression to respiratory failure. Assessing type and age at onset of airways problems and their evolution over time can support pediatricians in the diagnostic assessment of NMD. In addition, knowing the characteristics of patients' respiratory phenotype can increase the level of awareness among neonatologists, geneticists, neurologists, pulmonologists, nutritionists, and chest therapists, supporting them in the challenging task of the multidisciplinary medical care of patients. In this review we examine the issues related to the pediatric respiratory phenotypes of NMD and present a novel algorithm that can act as a guide for the diagnostic agenda and the key preventive or therapeutic interventions of airways manifestations. With prolonged survival of children with NMD, the advent of neuromuscular respiratory medicine, including accurate assessment of the respiratory phenotype, will help physicians to determine patients’ prognoses and to design studies for the evaluation of new therapies.